2019
DOI: 10.1159/000499131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Liners on Pulpal Outcome after Partial Caries Removal: A Preliminary 12 Months Randomised Controlled Trial

Abstract: Aim: The aim of this double-blinded parallel randomised controlled trial was to compare the effect of different liners on 12-month pulp health outcomes after partial caries removal (PCR) with composite restorations in permanent molars. Methods: The study was registered at clinicaltrials.gov with registration No. NCT0328695 and conducted in the Department of Conservative dentistry and Endodontics, Post Graduate Institute of Dental Sciences Rohtak with no external financial support. One hundred and ninety-eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
2
18
0
1
Order By: Relevance
“…Pulp protection or base/liner materials can be applied over the remaining demineralized dentin to promote the repair of carious dentin [ 4 ]. A clinical trial demonstrated that the use of liners was not directly associated with treatment success at 12 months [ 5 ]. However, clinicians who perform selective caries removal techniques still prefer to apply pulp protection materials over the remaining carious dentin [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pulp protection or base/liner materials can be applied over the remaining demineralized dentin to promote the repair of carious dentin [ 4 ]. A clinical trial demonstrated that the use of liners was not directly associated with treatment success at 12 months [ 5 ]. However, clinicians who perform selective caries removal techniques still prefer to apply pulp protection materials over the remaining carious dentin [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Os aspectos referentes à remoção do tecido cariado têm sido ressaltados em alguns estudos, que demonstram haver diferenças significativas entre as técnicas de remoção total, parcial e stepwise (Quadro 2). Tanto a remoção total quanto a remoção em dois passos clínicos do tecido cariado aumentam as chances de injúria e/ou comunicação pulpar (Maltz et al, 2012;Manton, 2013;Mattos et al, 2014;Hoefler et al, 2016;Villat et al, 2016;Zhang , 2017;Bjørndal et al, 2017;Maltz et al, 2018;Khokhar e Tewari, 2018;Giacaman et al, 2018;Singh et al, 2019;Ricketts et al, 2019;Pozos-guillén et al, 2021) Além disso, estudos também evidenciam que não há diferença estatisticamente diferentes quando do uso de materiais forradores ou inertes no selamento de cavidades profundas (Corralo e Maltz, 2013;Giacaman et al, 2018).…”
Section: Resultsunclassified
“… 20 About 88.1% of the respondents selected Ca(OH) 2 and GIC as the preferred materials used in pulpal lining that are in line with the recommendation and results showed from other studies. 21 22 23 Pulpotomy is a routinely performed clinical procedure with high clinical success to eliminate bacteria followed by the placement of a suitable material or medicament within the pulp chamber complex to maintain vitality of primary teeth until exfoliation to prevent the need of pulpectomy. 24 Approximately two-third of the respondents (74.9%) selected Ca(OH) 2 and ferric sulfate as the material of choice that is parallel with the current literature advocating material selection for pulpotomy.…”
Section: Discussionmentioning
confidence: 99%